PERENCANAAN PENGEMBANGAN EKOWISATA DI PANTAI BULBUL, BALIGE, SEBAGAI PEDOMAN PEMBUATAN PRODUK WISATA - Lyandru Togu Tambunan; Ivan Benedict Tambunan; Nirwaty Tarigan (Akademi Pariwisata Darma Agung, 2021)
This study is entitled Development Planning of Ecotourism in Bulbul Beach, Balige, as a Guidelines of Tourism Product. Researcher intend to research about the spatial and a-spatial actual condition in Bulbul Beach, and to know whether this actual condition is capable to be developed as an Ecotourism concept with the Sustainable Tourism as the guidelines for making of Tourism Product in the near future. From this research was found that the management of tourism facilities is still poor. Furthermore, by the physical and non-physical evidence of the actual condition of Bulbul Beach still significant to be developed with sustainable development guidelines for Tourism Product, with the use of Ecotourism planning principals.